Demonstration of the newly developed MTEM systems for gold detection in China. (3rd July 2019) - Di, Qingyun; Xue, Guoqiang; Lei, Da; Wang, Zhongxin; Li, Hai; Olalekan, Fayemi
Abstract : Previously, the multi‐channel transient electromagnetic (MTEM) system has been successfully developed and applied to hydrocarbon reservoirs exploration on land and offshore environments in France. In order to explore the mineral resources buried at the depths up to 2, 000 m in China, we developed a new MTEM system. In this paper, we present the components of the system, methods, principles, the parameters of the system, and the data interpretation method. To validate the effectiveness of the methodology and the developed system, we carried out an MTEM survey to locate the controlling faults of a gold deposit in the east of China. The survey contains 30 receivers distributed over 12‐km survey. By comparing the MTEM interpretation results with the known geological background, we find that MTEM methods can provide a good estimation of the ore‐controlling faults and this method could be a potential tool for the future deep mineral exploration.